2008
DOI: 10.1152/ajpgi.00144.2007
|View full text |Cite
|
Sign up to set email alerts
|

Protection of transplant-induced hepatic ischemia/reperfusion injury with carbon monoxide via MEK/ERK1/2 pathway downregulation

Abstract: Carbon monoxide (CO), a product of heme degradation by heme oxygenases (HO), has been shown to provide cytoprotection in various tissue injury models. This study examined the efficacy and molecular mechanisms of exogenously delivered inhaled CO in protecting liver grafts from cold ischemia/reperfusion (I/R) injury associated with liver transplantation. Orthotopic syngenic liver transplantation (OLT) was performed in Lewis rats with 18-h cold preservation in University of Wisconsin solution. Recipients were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 48 publications
7
71
0
1
Order By: Relevance
“…This suggests that there are additional mechanisms regulating c-Myc. c-Myc is also involved in some other pathway such as MAPK and ERK [Inamura et al, 2005;Kaizu et al, 2008]. Whether these pathways are redundant with down-regulation of c-Myc or cooperate in producing the down regulation in renal cell carcinoma stably expressed hepaCAM remains to be undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there are additional mechanisms regulating c-Myc. c-Myc is also involved in some other pathway such as MAPK and ERK [Inamura et al, 2005;Kaizu et al, 2008]. Whether these pathways are redundant with down-regulation of c-Myc or cooperate in producing the down regulation in renal cell carcinoma stably expressed hepaCAM remains to be undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CO inhalation bears the risk of adverse cardiac side-effects like dysrhythmia and decreased cardiac performance or even infarction. Using the rat liver transplantation model, it has been reported that brief recipient CO inhalation during the peritransplant period ameliorates liver graft damage and inhibits pro-inflammatory responses during transplant-induced cold hepatic IRI [139]. Inhalation of CO at a low concentration provides protection of kidney grafts against cold IRI and preserves overall improved kidney graft functioning following transplantation [140].…”
Section: Pharmacological Manoeuvresmentioning
confidence: 99%
“…More recent data have shown that HO-1 modulates pro-inflammatory responses that are triggered via TLR4 signaling, a putative HO-1 repressor [48] . The role of CO in protecting liver grafts from cold I/R injury associated with liver transplantation has been studied by Kaizu et al [49] . Inhalation of CO reduces hepatic injury and is associated with marked downregulation of early mRNA expression for tumor necrosis factor TNF-α, interleukin IL-6, and NOS.…”
Section: Heme Oxygenase Confers Protection Versus Different Types Of mentioning
confidence: 99%